Clinical analysis of four serum tumor markers in 458 patients with ovarian tumors: diagnostic value of the combined use of HE4, CA125, CA19-9, and CEA in ovarian tumors - Chen F (Cancer Management and Research, 2018)
Fawen Chen,1,2 Jing Shen,3 Jianwei Wang,1 Pengwei Cai,1 Yi Huang3 1Department of Clinical Laboratory, Fujian Provincial Hospital South Branch, 2Department of Blood Transfusion, 3Department of Clinical Laboratory, Fujian Provincial Hospital, Provincial Clinical College of Fujian Medical University, Fuzhou, People’s Republic of China Purpose: To investigate the diagnostic values of human epididymis protein 4 (HE4), carbohydrate antigen 125 (CA125), carbohydrate antigen 19-9 (CA19-9), and carcinoembryonic antigen (CEA) for ovarian tumors. Methods: The participants were divided into three groups: 386 healthy women (control group), 262 patients with benign ovarian tumors (the benign group), and 196 patients with malignant pelvic tumors (the malignant group). The serum levels of HE4, CA125, CA19-9, and CEA were analyzed by electrochemiluminescent immunoassay. Results: It showed that serum levels of HE4, CA125, CA19-9, and CEA of patients with malignant ovarian tumors were significantly higher than those in the control group and benign group (P<0.01). HE4 had a high specificity (96.56%) in malignant ovarian tumors. The tumor markers HE4, CA125, CA19-9, and CEA had a sensitivity of 63.78%, 62.75%, 35.71%, and 38.78%, respectively. The combined use of two or more tumor markers (parallel test) had a higher diagnostic sensitivity but lower specificity than a single tumor marker. The combined efficiency of HE4 and CA125 was the highest, with a sensitivity and specificity of 80.10% and 69.08%, respectively. HE4 and CA125 combined with the Risk of Ovarian Malignancy Algorithm provided an efficient means of screening and diagnosis of ovarian malignancies. The diagnostic sensitivity increased to 88.52% when three or four tumor markers were used but showed no significant difference compared with the combination of HE4 and CA125 (P>0.05). Conclusion: The combination of three or four tumor markers did not improve the diagnostic efficacy when compared with the combination of HE4 and CA125. Keywords: human epididymis protein 4, carbohydrate antigen 125, carbohydrate antigen 19-9, carcinoembryonic antigen, pelvic tumor